Firm characteristics, competitive strategies, environment and business performance: survey evidence from Malaysian SMEs - Hashim, Mohd Khairuddin; Wafa, Syed Azizi; Sulaiman, Mohamed (Universiti Utara Malaysia, 2000)
This article focuses on small and medium-sized enterprises (SMEs) from the strategic management perspective. This article is based on the findings of a sample survey that examined the general relationships between firm characteristics, competitive strategies,environment and business performance of SMEs in the Malaysian manufacturing sector.The sample consisted of 100 SMEs from different industries. The empirical findings suggested different patterns of competitive strategies and performance relations as well as the relationships between firm characteristics, environment and the business performance of the SMEs surveyed.